Subwavelength angle-sensing photodetectors inspired by directional hearing in small animals. Issue 12 (December 2018) - Yi, Soongyu; Zhou, Ming; Yu, Zongfu; Fan, Pengyu; Behdad, Nader; Lin, Dianmin; Wang, Ken; Fan, Shanhui; Brongersma, Mark
Abstract Sensing the direction of sounds gives animals clear evolutionary advantage. For large animals, with an ear-to-ear spacing that exceeds audible sound wavelengths, directional sensing is simply accomplished by recognizing the intensity and time differences of a wave impinging on its two ears1 . Recent research suggests that in smaller, subwavelength animals, angle sensing can instead rely on a coherent coupling of soundwaves between the two ears2–4 . Inspired by this natural design, here we show a subwarvelength photodetection pixel that can measure both the intensity and incident angle of light. It relies on an electrical isolation and optical coupling of two closely spaced Si nanowires that support optical Mie resonances5–7 . When these resonators scatter light into the same free-space optical modes, a non-Hermitian coupling results that affords highly sensitive angle determination. By straightforward photocurrent measurements, we can independently quantify the stored optical energy in each nanowire and relate the difference in the stored energy between the wires to the incident angle of a light wave. We exploit this effect to fabricate a subwavelength angle-sensitive pixel with angular sensitivity, δθ = 0.32°. Two Si resonators couple through a non-Hermitian interaction to sense both the intensity and the incident angle of light with subwavelength resolution.